INTERPERSONAL COMMUNICATION TO OVERCOME OBSTACLES IN THE DIFFERENT CASTE MARRIAGE OF BALI COMMUNITY IN NAMBARU VILLAGE - Raningsih, Kadek (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
This study aims to determine how interpersonal communication is used to overcome obstacles that occur in different caste marriages in Nambaru Village. This type of research is descriptive qualitative research. To answer the existing problems, the methodological process consists of Library Research and Field Research. The author uses the technique of collecting data through observation, interviews, and documentation. To get the primary data in the field, the informants were determined purposively as many as 5 informants, all of whom were Nambaru Village residents. From the results of the study provide an overview of interpersonal communication that is used in overcoming obstacles that occur in different caste marriages by a pragmatic approach which is part of the effectiveness in communication that is being confident, togetherness, management interaction, expressive behavior and orientation to others. Aside from the pragmatic approach to success in fostering a household it is also influenced by several internal and external factors, where internal factors occur because both parties love each other, ways of thinking and education. While the external factor consists of the development of the times and environmental influences.